2020
DOI: 10.1101/2020.06.17.158006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic surveillance of SARS-CoV-2 reveals community transmission of a major lineage during the early pandemic phase in Brazil

Abstract: 42

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 38 publications
4
30
0
2
Order By: Relevance
“…SARS-CoV-2 genome sequence submission to the Pangolin and CoV-GLUE algorithms resulted in the same lineage classification in all cases, defining all but one virus belonging to clade B1.1, while the remaining sequence was classified as B.1. A phylogenetic analysis of the viruses together with sequences previously defined as Brazilian circulating strains B1.1-BR and B1.1-EU/BR showed that most B1.1 genomes generated in this study clustered with B1.1-BR sequences ( Fig 1A) [16]. A phylogenetic tree including all local SARS-CoV-2 sequences isolated from patients residing in the state of Rio de Janeiro available at the GISAID database (accessed on July 27th, 2020, S1 Table) was performed to investigate potential epidemiological linkage between samples ( Fig 1B).…”
Section: Phylogenetic and Epidemiological Profile Of Sars-cov-2 Sequementioning
confidence: 54%
See 1 more Smart Citation
“…SARS-CoV-2 genome sequence submission to the Pangolin and CoV-GLUE algorithms resulted in the same lineage classification in all cases, defining all but one virus belonging to clade B1.1, while the remaining sequence was classified as B.1. A phylogenetic analysis of the viruses together with sequences previously defined as Brazilian circulating strains B1.1-BR and B1.1-EU/BR showed that most B1.1 genomes generated in this study clustered with B1.1-BR sequences ( Fig 1A) [16]. A phylogenetic tree including all local SARS-CoV-2 sequences isolated from patients residing in the state of Rio de Janeiro available at the GISAID database (accessed on July 27th, 2020, S1 Table) was performed to investigate potential epidemiological linkage between samples ( Fig 1B).…”
Section: Phylogenetic and Epidemiological Profile Of Sars-cov-2 Sequementioning
confidence: 54%
“…For SARS-CoV-2 lineage classification, consensus genomes were submitted to Pangolin software (https://github.com/cov-lineages/pangolin, downloaded on June 10 th , 2020) and to CoV-GLUE lineage system (http://cov-glue.cvr.gla.ac.uk/#/home, accessed on June 10 th , 2020) [25], both based on the nomenclature proposed by Rambaut et al [26]. An alignment including the consensus sequences generated and genomes from Brazilian sequences available on the GISAID Database classified as B1, B1.1 and the Brazilian clusters B1.1-BR/ B1.1-EU/BR (S1 Table) were submitted to a maximum likelihood phylogenic reconstruction using PhyML v.3.0 and the best model of nucleotide substitution was defined with Model Generator (GTR) to investigate the sublineage classification of the study sequences [16,27,28]. Furthermore, a phylogenetic analysis that included the generated consensus sequences generated along with all SARS-CoV-2 sequences from Rio de Janeiro state (Brazil) presently available at GISAID (https://www.epicov.org/epi3/frontend, accessed on July 27 th , 2020, S1 Table) was performed in order to investigate epidemiological relatedness of sequences.…”
Section: Sars-cov-2 Classification and Phylogenetic Analysismentioning
confidence: 99%
“…For Spain, NYC and Brazil, the TN10 projections point the origin of local viral transmissions 10-15 days earlier than the estimated T MRCA of major transmission lineages detected (Table). (11,13,22,23) For UK and Belgium, by its turn, the TN10 and TN100 projections recovered dates that were 15-20 days earlier than the estimated T MRCA of local lineages detected (Table). (14,17) The T MRCA of local SARS-CoV-2 transmission lineages in France, Germany and Netherlands were not described so far.…”
mentioning
confidence: 95%
“…1B) can be inferred using published estimates of the evolutionary rate of the SARS-2 population in the human population, assuming that the pre-and post-emergence rates are the same (Rodríguez-Román and Gibbs, 2020). Various estimates of the SARS-2 evolutionary rate have been published recently; 1.126 x 10 -3 (95 % BCI: 1.03-1.23 x 10 -3 ) substitutions per site per year (s/s/y) (Candido et al, 2020), 1.1×10 −3 s/s/y (95% CI 7.03×10 −4 and 1.5×10 −3 s/s/y) (Duchêne et al, 2020), 9.41×10 -4 s/s/y +/-4.99×10 -5 (Pybus et al, 2020) and 8 x 10 -4 s/s/y (Resende et al, 2020).…”
Section: Resultsmentioning
confidence: 99%